Pengembangan E-LKPD Berbasis Problem Based Learning (PBL) dalam Meningkatkan Keterampilan Berpikir Kritis Pada Materi Sistem Peredaran Darah Kelas XI IPA di SMA Negeri 1 Lau Baleng - Maha, Destri Br; Manalu, Kartika (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to develop an E-LKPD based on Problem Based Learning (PBL) by utilizing the Liveworksheet platform to improve the critical thinking skills of grade XI IPA students at SMA Negeri 1 Lau Baleng. The study used the Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate). The research subjects involved 31 grade XI IPA F2 students and one biology teacher. The product was validated by material and media experts with results of 90.62% and 88.75%, respectively (very valid category). The practicality test showed a teacher response of 100% and a student response of 95.72% (very practical category). The effectiveness of E-LKPD was demonstrated through the N-Gain analysis = 0.74 (high category). The research findings indicate that (1) the results of expert validation on content, media, and assessment items fall into the Very Valid category; (2) teacher responses reached 100% and student responses 95.72%, both categorized as Very Practical; (3) the results of the pretest and posttest showed an improvement in critical thinking skills with an N-Gain score of 0.74 (high category). Therefore, the PBL-based E-LKPD using Liveworksheet is feasible, practical, and effective for use in biology learning on the circulatory system material.